Progesterone-induced gene expression profile of the filamentous fungus Cochliobolus lunatus - Berne, Sabina (Acta chimica slovenica, 2008)
Suppression subtractive hybridization (SSH) was employed to study differential gene expression upon progesterone treatment of the filamentous fungus Cochliobolus lunatus, a plant and opportunistic human pathogen. The transcription profile of progesterone-induced vs. non-induced C. lunatus revealed changes in the number of genes involved in facilitated and vesicle mediated transport, amino acid and derivative metabolism, protein biosynthesis, cell wall biogenesis, lipid metabolism, carbohydrate metabolism,and generation of precursor metabolites and energy. These results suggest that progesterone induces a global adaptive stress response in the organism. Such a response is not surprising, as the steroidal ring structure is similar to certain antifungal plant defense compounds. In C. lunatus, the conversion of such molecules to hydroxylated and less-toxic substances is mediated by enzymes of the cytochrome P450 superfamily, however little is known of the genes encoding them. We identified several putative cytochrome P450 cDNA sequences and quantitatively analyzed their relative mRNA levels upon progesterone induction using Real-time RT-PCR. None of the selected cytochromes P450 showed significant up-regulation (more than 2 fold induction). As an additional inevitable consequence of the large-scale sequencing of cDNA clones, valuable insight into the genome of this non-model organism was obtained
Keywords: biokemija; citokrom P-450; Cochiobolus lunatus; encimi; izražanje genov; nitaste glive; progesteron; Progesterone